The Peugeot Center Model and Mentoring Explored through a Case Study of the Design and Installation of a Potable Water System in Guatemala with ADICAY - Dodson, Kirsten Heikkinen; Baugh, Daniela; Roland, Avery; Edmonds, Sara; York, Hannah Pinson (Advances in engineering education, 2022)
At the Peugeot Center for Engineering Service in Developing Communities at Lipscomb University, seventeen years of experience have provided the foundation for a program that creates lasting impact. In comparison to other service learning or humanitarian engineering programs, the Peugeot Center is unique in that it achieves substantial impact on students, communities, and engineering professionals. This paper describes the model and mentoring employed by the Peugeot Center with supporting examples from a recent project. The case study describes a potable water system that was designed by a team of students, a professional engineer, and a partnering organization in Guatemala called ADICAY. Though the professional engineer and ADICAY supported the overall design work, the students supported the project by completing a site survey, designing the piping layout, and leading the onsite construction. Through mentoring from the professional engineer, the students developed skills in project management, teamwork, communication, and ethical decision-making. The professional engineer noted the opportunity to use their engineering skills to serve others as a primary reason for involvement. By partnering with ADICAY, the students learned about the complex cultural, social, economic, and environmental impacts of their engineering work. The installed system provides potable water to 113 household taps in a rural Mayan community. A medical clinic held before and after the installation of the water system showed a reduction in water-borne illness diagnoses from 40% to 11%. Additionally, data from the clinic showed a lower rate of waterborne illness diagnoses in Setzimaaj (11%) compared to surrounding communities without potable water (33%). Overall, the success of the project is attributed to significant mentoring as well as the deep trust that was built in these partnerships. Lessons learned and best practices for employing a model similar to the Peugeot Center's are reflected throughout the paper.